2011
DOI: 10.1002/ajim.20849
|View full text |Cite
|
Sign up to set email alerts
|

Work‐related fatalities among youth ages 11–17 in North Carolina, 1990–2008

Abstract: Although the prevalence of adolescent work-related fatalities has seen a decline in North Carolina, the 31 deaths we detected signal a failure of the systems in place to prevent young worker fatalities. More remains to be done to protect the lives of adolescent workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…While this is consistent with past studies [Estes et al, 2010;Steege et al, 2014], our findings also revealed foreign-born youth, the majority of whom come from Mexico and Central America, were at the greatest risk of suffering an occupational fatality when compared to those born in the US. Consistent with prior studies, our results showed transportation incidents and vehicles are the number one event/exposure and source, respectively, of fatal injury to teens [Dunn and Runyan, 1993;Estes et al, 2010;Rauscher et al, 2011;Steege et al, 2014].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…While this is consistent with past studies [Estes et al, 2010;Steege et al, 2014], our findings also revealed foreign-born youth, the majority of whom come from Mexico and Central America, were at the greatest risk of suffering an occupational fatality when compared to those born in the US. Consistent with prior studies, our results showed transportation incidents and vehicles are the number one event/exposure and source, respectively, of fatal injury to teens [Dunn and Runyan, 1993;Estes et al, 2010;Rauscher et al, 2011;Steege et al, 2014].…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with prior studies [Estes et al, 2010], we found the rate of occupational fatalities among 15-to 17-year-olds has dropped since 2001. Our findings also suggest the gender differences seen in past studies of teen occupational fatalities [Dunn and Runyan, 1993;Higgins et al, 2002;Estes et al, 2010;Rauscher et al, 2011;Steege et al, 2014] continue to persist, with 15-to 17-year old males experiencing a significantly higher fatality rate compared to females. Another significant finding from this study relates to Hispanic youth ages 15-17 who had higher fatality rates than their white counterparts.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…(27) That study provides the population of fatality cases used in the current analysis (further details on case ascertainment and data collection are discussed below).…”
Section: Methodsmentioning
confidence: 99%
“…Case characteristics of all 31 decedents as well as further details on data collection can be found elsewhere. (27) Death certificate data for all decedents were manually extracted from hard copies that were filed by the medical examiner with the North Carolina Office of Vital Statistics.…”
Section: Data Collection and Study Populationmentioning
confidence: 99%